# SOLUTION: I have a problem that asks me to simplify the algebraic expression. 3(x-1)(x+4)-2(3x-4) I distributed out the 3 and -2 and then foiled them out and combined like terms but non

Algebra ->  Algebra  -> Expressions -> SOLUTION: I have a problem that asks me to simplify the algebraic expression. 3(x-1)(x+4)-2(3x-4) I distributed out the 3 and -2 and then foiled them out and combined like terms but non      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Evaluation of expressions, parentheses Solvers Lessons Answers archive Quiz In Depth

 Question 542537: I have a problem that asks me to simplify the algebraic expression. 3(x-1)(x+4)-2(3x-4) I distributed out the 3 and -2 and then foiled them out and combined like terms but none of my answer choices match up to my answer! I need help please! The answer choices are: A. 3x^2 +9x -4 B. 3x^2 +3x -20 C. 3x^2 +3x -16 D. 3x^2 +3x -4Answer by stanbon(57307)   (Show Source): You can put this solution on YOUR website! 3(x-1)(x+4)-2(3x-4) --- 3(x^2+3x-4)-6x+8 --- 3x^2+9x-12-6x+8 --- 3x^2+3x-4 ----------------- Cheers, Stan H. ================= The answer choices are: A. 3x^2 +9x -4 B. 3x^2 +3x -20 C. 3x^2 +3x -16 D. 3x^2 +3x -4